Presence and Potential Effect of Microplastics Associated with Anthropic Activity in Two Benthic Fishes Serranus scriba and Lithognathus mormyrus - Amanda Cohen-Sánchez; Juan Alejandro Sanz; Montserrat Compa; Maria Magdalena Quetglas-Llabrés; Maria del Mar Ribas-Taberner; Lorenzo Gil; Silvia Tejada; Samuel Pinya; Antoni Sureda (Fishes)
Plastic pollution poses a massive problem to the environment, particularly seas and oceans. Microplastics (MPs) ingestion by marine species can generate many adverse effects, including causing oxidative stress. This study evaluated the effects of anthropic activity-related MP presence in two coastal fish species—Serranus scriba (more related to rocky bottoms) and Lithognathus mormyrus (more related to sandy bottoms)—in two areas of Mallorca Island (Western Mediterranean) with varying anthropic pressures with similar mixed rocky/sandy bottoms. A total of eight fish samples per species and per area (total n = 32), as well as three water samples (500 mL each) and three sediment samples per area, were collected and analyzed. The results showed that despite plastic presence in both areas, the area with higher tourism affluence was also the most polluted. Fourier transform infrared spectroscopy analysis confirmed that the majority of recovered polymers were polyethylene and polypropylene. The pattern of MPs presence was reflected in the biomarker analysis, which showed higher values of antioxidants, namely catalase (CAT) and superoxide dismutase (SOD); detoxification, namely glutathione s-transferase (GST); and inflammation, namely myeloperoxidase (MPO)—enzymes in the gastrointestinal tract of fish from the more polluted area. However, no statistical differences were found for malondialdehyde (MDA) as a marker of lipid peroxidation. As for differences between species, S. scriba presented a higher presence of MPs and measured biomarkers than in L. Mormyrus, suggesting higher exposure. In conclusion, these results showed that increased anthropic activity is associated with a higher presence of MPs which, in turn, induces an adaptative response in exposed fish. Moreover, species living in the same area could be differentially affected by MPs, which is probably associated with different behavioural and feeding habits.